2018
DOI: 10.21743/pjaec/2018.12.11
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite in Nature: Determination with Polymeric Materials

Abstract: Nitrogen compounds being important for the vital activities of living things are produced by the nitrification process and occurred spontaneously in the nitrogen cycle. Human vital activities are also responsible for the extra nitrogen released into the atmosphere. So, both human and environmental healths are negatively affected by the increasing nitrate and nitrate amounts in water and soil. For this reason, it is aimed to ensure regular control of nitrates and nitrites at certain levels in order to protect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Changes in nutrient concentrations in inflow and outflow provided information about the uptake of ions by plants and provided feedback about the nutrient needs of plants to be met. Selected applications of polymeric materials for nitrite assessment in nature, with particular attention on sensing materials' compositions and performances, are overviewed by Yenil and Yemiş in [57].…”
Section: Total and Mineral Nitrogenmentioning
confidence: 99%
“…Changes in nutrient concentrations in inflow and outflow provided information about the uptake of ions by plants and provided feedback about the nutrient needs of plants to be met. Selected applications of polymeric materials for nitrite assessment in nature, with particular attention on sensing materials' compositions and performances, are overviewed by Yenil and Yemiş in [57].…”
Section: Total and Mineral Nitrogenmentioning
confidence: 99%
“…The first stage is the formation of nitrite (NO 2 ), and the second stage is nitration, that is, the conversion from nitrite into nitrate form (NO 3 ) [23,24]. A study on Swiftlet feces and air conditions using 16S rRNA in an SFH of Sarawak, Malaysia, detected the gram-positive pathogenic bacteria Bacillus, Lysinibacillus, Paenibacillus, and Sporosarcina [25]. Analysis of the air samples of SFH in Malaysia using 16S rRNA sequencing revealed 27 species of airborne bacteria, with Lysinibacillus spp., being the most common.…”
Section: It Can Increase Cancer Risk Factors Due To Carcinogenicmentioning
confidence: 99%
“…However, analyses of the last 5 years of publications on NO 2 − -sensor development have shown that less than 10% of all research is dedicated to sensors with optical transduction; this research is mainly dedicated to nanomaterial-based sensors, such as metal and metal-oxide nanoparticles [12,13], quantum dots [14], or liquid crystals [15]. Some applications of polymeric sensing materials doped with nitrite-selective ligands for optode development are also reported [16]. The accurate selection of the appropriate macromolecular ligands selectively binding to the target analyte has permitted the development of selective optodes for several inorganic anions, including nitrites [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%